1996
DOI: 10.1002/hep.510230102
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative responses to hepatitis C virus core, E1, E2, and NS3 in patients with chronic hepatitis C infection treated with interferon alfa

Abstract: , and NS3 were recognized HCV-specific CD8/ cytotoxic T lymphocytes (CTL) able less frequently. This recognition pattern was not related to recognize and kill target cells expressing core, E1, to the therapy with IFN-a nor to the clinical response E2, and NS2 proteins in an HLA class I restricted manof the patient toward this therapy. The response to the ner, could be isolated from liver tissue of chronic hepaCore protein could be fine-mapped to the COOH-termi-titis C patients. [5][6][7] In addition, periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
28
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 22 publications
18
28
0
Order By: Relevance
“…IL-21 is also required for viral control in chronic viral infection (Elsaesser et al, 2009). In addition, some studies have shown CD4+ T cell responses to core protein in CHC patients (Leroux-Roels et al, 1996). Therefore, we analyzed the relationship between HCV core peptide pool-specific IL-21+CD4+ T cells and HCV RNA viral load.…”
Section: Discussionsupporting
confidence: 48%
“…IL-21 is also required for viral control in chronic viral infection (Elsaesser et al, 2009). In addition, some studies have shown CD4+ T cell responses to core protein in CHC patients (Leroux-Roels et al, 1996). Therefore, we analyzed the relationship between HCV core peptide pool-specific IL-21+CD4+ T cells and HCV RNA viral load.…”
Section: Discussionsupporting
confidence: 48%
“…Their importance has also been confirmed in the chimpanzee model [11,12]. Based on these observations, HCVspecific CD4 + T cell epitopes have been identified in infected patients [7,10,[13][14][15][16][17][18][19][20][21] with the final attempt to select peptides to be included in epitope-based vaccines or to be used for the development of tetramers. However, the identified sequences in NS3 and NS4 cover more than 60% of the proteins [21] and many of the HCV T cell epitopes were found to be specific to one patient only [7].…”
Section: Introductionsupporting
confidence: 45%
“…5,6 The choice of E1 as immunogen was based on a number of observations. Humoral and cellular immune responses to the E1 protein are largely impaired in patients with chronic active hepatitis C. 7 Antibody responses to the E1 protein are usually weak and cellular immune responses are almost absent in patients with chronic active hepatitis C. 8 Furthermore, baseline E1 antibody levels are higher in sustained responders than in nonresponders to interferon-α-based treatment, suggesting a beneficial effect of a pre-existing anti-E1 immune responses on the clearance of infection. [9][10][11] Finally, E2 has the disadvantage of displaying a very high strain-to-strain variation in the immunodominant hypervariable region 1, and E1 also has a higher degree of inter-genotype cross-reactivity as compared to E2 (our unpublished data).…”
Section: Introductionsupporting
confidence: 43%